Some remarks on selfnormalization for a simple spatial autoregressive model - Zovė, Romas (Lietuvos matematikos rinkinys, 2021)
In the paper I continue investigations on the self-normalization of simple autoregressive field Xt,s = aXt−1,s + bXt,s−1 + εt,s started in [5]. And extend previous results when the variance of the innovations of the process above are not finite.
Keywords: autoregressive models; self-normalization; random fields